Feasibility study of the BrightBrainer™ integrative cognitive rehabilitation system for elderly with dementia. (September 2015) - Burdea, Grigore; Polistico, Kevin; Krishnamoorthy, Amalan; House, Gregory; Rethage, Dario; Hundal, Jasdeep; Damiani, Frank; Pollack, Simcha
Abstract Purpose: To describe the development of BrightBrainer™ integrative cognitive rehabilitation system and determine clinical feasibility with nursing home-bound dementia patients. Method: BrightBrainer cognitive rehabilitation simulations were first played uni-manually, then bimanually. Participants sat in front of a laptop and interacted through a game controller that measured hand movements in 3D, as well as flexion of both index fingers. Interactive serious games were designed to improve basic and complex attention (concentration, short-term memory, dual tasking), memory recall, executive functioning and emotional well-being. Individual simulations adapted automatically to each participant's level of motor functioning. The system underwent feasibility trials spanning 16 sessions over 8 weeks. Participants were evaluated pre- and post-intervention, using standardized neuropsychological measures. Computerized measures of movement repetitions and task performance were stored on a remote server. Results: Group analysis for 10 participants showed statistically significant improvement in decision making (p < 0.01), with trend improvements in depression (p < 0.056). Improvements were also seen in processing speed (p < 0.13) and auditory attention (p < 0.17); however, these were not statistically significant (partly attributable to the modest sample size). Eight of nine neuropsychological tests showed changes in the improvement direction indicating an effective rehabilitation (p < 0.01). BrightBrainer technology was well tolerated with mean satisfaction ratings of 4.9/5.0 across participants. Conclusions: Preliminary findings demonstrate utility within an advanced dementia population, suggesting that it will be beneficial to evaluate BrightBrainer through controlled clinical trials and to investigate its application in other clinical populations. Implications for Rehabilitation It is possible to improve cognitive function in older low-functioning patients. Integrative rehabilitation through games combining cognitive (memory, focusing, executive function) and physical (bimanual whole arm movement, grasping, task sequencing) elements is enjoyable for this population. The severity of depression in these elderly can be reduced through virtual reality bimanual games. The number of upper extremity active repetitions performed in the process of solving cognitive problems with the BrightBrainer™ system is 600. This number is 18 times (1875%) larger than those observed by other researchers in conventional physical or occupational rehabilitation sessions.